Rurality and Outcomes of Patients Undergoing Mechanical Thrombectomy for Acute Ischemic Stroke - Cassidy Lavin; Jacob Epstein; Alvin Huanwen Chen; Minahil Cheema; Jerry Yang; Alexa Aquino; Angie Chan; Nancy Le; Gillian Cooper; Ambra Palushi; Chad Schrier; Dheeraj Gandhi; et al. (Critical Care Research and Practice)
Conclusions: Patients transferred from rural areas for MT for AIS-LVO, at our institution, had a similar likelihood of achieving 90-day mRS 0–2 as those transferred from urban areas.